Regional Integration in Africa: Progress of Agenda 2063 - Siphesihle , Nene (Studia Mundi – Economica, 2024)
Regional integration in Africa is a multifaceted process involving economic, political, and social dimensions. The African Union, established in 2002, has emerged as a key actor in fostering cooperation among African nations. The development of Agenda 2063 by the African Union serves as a strategic framework aimed at fostering socio-economic development and regional integration throughout the continent, addressing the diverse challenges confronting African countries. However, with the conclusion of the initial phase of Agenda 2063 in 2023, it is evident that many African countries are struggling to achieve the set goals. The attainment of these objectives appears to be beyond the reach of most African countries, with projections indicating that they may only materialize well beyond the target year of 2063. This paper critically examines the progress made by the African Union in implementing regional policies during the first decade and assesses the challenges encountered in promoting cohesive regional governance to realize the objectives outlined in Agenda 2063 in Southern Africa.